Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.7567/jjap.56.086501
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of Schottky barrier diodes fabricated on (001) β-Ga2O3substrates with crystal defects

Abstract: The electrical properties of Schottky barrier diodes (SBDs) on a (001) β-Ga2O3 substrate were characterized and correlated with wet etching-revealed crystal defects below the corresponding Schottky contacts. The etching process revealed etched grooves and etched pits, indicating the presence of line-shaped voids and small defects near the surface, respectively. The electrical properties (i.e., leakage currents, ideality factor, and barrier height) exhibited almost no correlation with the density of the line-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 32 publications
(54 reference statements)
1
51
0
Order By: Relevance
“…Most previously reported diode rectifiers have had areas of less than 10 −3 cm 2 and this effect will not be obvious in that situation [7], [17]- [19]. Oshima et al [37] found a spatial correlation between dicing-induced defects and large reverse leakage currents in diodes fabricated in those areas on (001) oriented substrates. Kasu et al [36] reported densities of etch pits above 10 4 cm −2 whose presence did not directly correlate with increased reverse leakage current in similar diodes on (001) oriented substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Most previously reported diode rectifiers have had areas of less than 10 −3 cm 2 and this effect will not be obvious in that situation [7], [17]- [19]. Oshima et al [37] found a spatial correlation between dicing-induced defects and large reverse leakage currents in diodes fabricated in those areas on (001) oriented substrates. Kasu et al [36] reported densities of etch pits above 10 4 cm −2 whose presence did not directly correlate with increased reverse leakage current in similar diodes on (001) oriented substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Several authors are conducting early-stage research on β-Ga 2 O 3 -based Schottky barrier diodes (SBDs). A few studies on β-Ga 2 O 3 SBDs fabricated on β-Ga 2 O 3 single crystal grown by different growth methods with various crystal orientations have been reported in the literature [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Most of these studies investigated the electrical characteristics in forward bias conditions where the thermionic emission (TE) mechanism is predominant.…”
Section: Introductionmentioning
confidence: 99%
“…Our case of 8 μm with doping 4.4 × 10 15 cm −3 has a theoretical breakdown more than an order of magnitude larger than the experimental value. 43,44…”
Section: Resultsmentioning
confidence: 99%